Uzbekistan-made biometric plant detectors for hazardous substance identification - Rakhimov Abdulla; Ismoyilov Alisher; Oblokulov Feruz; Kiryigitova Sevara; Mavlonova Dildora; Soatova Sodira (BIO Web of Conferences)
This article provides information on the complex assessment of the morpho-biological and value-added characteristics of non-conventional vegetable varieties grown in the irrigated soil-climatic conditions of Samarkand region, as well as on the study of their growth and development properties. With the availability of opportunities to increase the production of sustainable vegetables for export, the use of agrotechnology is of great importance in the correct selection of new and secondary crops, depending on the biological characteristics of the crop. The purpose of the study is to conduct a complex assessment of the morpho-biological and value-economic signs of the most suitable varieties and samples for the soil-climatic conditions of the republic, to study the characteristics of growth and reproduction. The tasks of the research are to select the most acceptable samples for the soil-climatic conditions of the region on the basis of a complex assessment of the morpho-biological and value-economic signs of the susceptible new samples, to study their growth, reproduction, yield of new varieties, as well as the methods of preparation of seedlings.